Caracterización físico química del aceite esencial de la muña (mynthostachis setosa) y su estudio antibacteriano. - Quispe Sánchez, Joan Pierre (2015)
The objective of this paper is to demonstrate the physical, chemical characteristics present in the essential oil of Muña (Minthostachys setosa), from the province of Yauyos, Department of Lima, as well as establishing the antibacterial effect and minimum inhibitory concentration at which, the above mentioned essential oil is active against pathogens of medical and nutritional importance. characterize physically and chemically essential oil of Muña (Minthostachys setosa), as well as establishing minimum inhibitory concentrations at which the essential oil is active against bacteria of medical and food importance. The essential oil of the leaves of Minthostachys Setosa (Muña) has been extracted by hydrodistillation method. This was subjected to physical-chemical analysis such as Refractive Number, Solubility in Ethanol, Ester Number, Acid Number, etc. And, by planting Zig-Zag method, the antibacterial effect and MIC was determined for: Enterococcus faecalis, aureuginosa Pseudomonas, Escherichia coli, Streptococcus mutans and Staphylococcal aureus. Determining that the essential oil of Muña can be extracted industrial scale to be used as a natural antioxidant in food processing, besides having antibacterial properties against Enterococcus faecalis, Staphylococcal aureus, Escherichia coli and Streptococcus mutans, since its growth was inhibited by the essential oil.